2021
DOI: 10.1111/aji.13493
|View full text |Cite
|
Sign up to set email alerts
|

Increased uterine NLRP3 inflammasome and leucocyte infiltration in a rat model of preeclampsia

Abstract: The disruption of the inflammatory microenvironment in the uterus affects pregnancy outcome. However, the exact quantification and distribution of leukocyte subpopulations in the uterus in preeclampsia (PE) have not been clearly characterized. Inflammasomes promote the release of proinflammatory cytokines interleukin (IL)‐β and IL‐18. A higher expression of NLRP3 inflammasome in placentas contributes to excessive inflammation in PE. However, related studies on the uterus are scarce. We aimed to investigate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…There is a high level of NLRP3 expression in granulosa cells from patients with ovarian insufficiency, and the NLRP3 inflammasome has negative effects on female fertility ( 45 ). Activating the NLRP3 inflammasome disrupts the inflammatory microenvironment in the uterus, which leads to excessive inflammation at the maternal–fetal interface in rat preeclampsia ( 46 ). The NLRP3 inflammasome is activated in the myometrium tissues and amnion and chorion deciduas, which are associated with labor onset at term and preterm in humans and mice ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a high level of NLRP3 expression in granulosa cells from patients with ovarian insufficiency, and the NLRP3 inflammasome has negative effects on female fertility ( 45 ). Activating the NLRP3 inflammasome disrupts the inflammatory microenvironment in the uterus, which leads to excessive inflammation at the maternal–fetal interface in rat preeclampsia ( 46 ). The NLRP3 inflammasome is activated in the myometrium tissues and amnion and chorion deciduas, which are associated with labor onset at term and preterm in humans and mice ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of evidence now suggests that the NLRP3 inflammasome plays a pivotal role in the mechanism of inflammatory complications during pregnancy. Zeng et al found that the activation of NLRP3 inflammasome in the uterus is responsible for the excessive inflammation at the maternal–fetal interface during PE [ 44 ]. The NLRP3 inflammasome processes an increased “danger” of cytokines after the NLRP3 is activated.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of PreE animal models have been used to provide more insight into immunological mechanisms associated with PreE [38][39][40]. A study by Zeng et al which utilized a PreE rat model reported that PreE rats had higher mRNA expression of NLRP3 in uterine tissues compared to normal pregnant rats [41]. This group also found that both uterine protein expression of caspase-1 along with mRNA expression of caspase-1 and IL-1β were increased, leading them to conclude that the NLRP3 inflammasome has a key role in regulating uterine inflammation.…”
Section: Preclinical Studiesmentioning
confidence: 99%